2000
DOI: 10.1603/0022-0493-93.2.293
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory and Field Evaluations of Imidacloprid AgainstMelanoplus sanguinipes(Orthoptera: Acrididae) on Small Grains

Abstract: The toxicity of imidaloprid to the migratory grasshopper, Melanoplus sanguinipes (F.), was measured in bioassays, greenhouse trials, and field trials. An LD50 of 53 and 86 ppm for the oral/topical applications of imidacloprid confirmed a low toxicity for this chemical when compared with carbofuran as a standard. However, 100% debilitation was observed at concentrations of > or = 1 ppm. Grasshoppers exhibited leg flexing, abdominal quivering, and tremors before becoming motionless and appearing dead. Knockdown … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 18 publications
0
10
0
Order By: Relevance
“…These values are near or below those estimated for imidacloprid in other insects. Thus, the LD 50 of imidacloprid in the migratory grasshopper, Melanoplus sanguinipes (F.), was 53 mg/l for the oral applications (Tharp et al. 2000), while its LC 50 in the adult whiteflies collected from Arizona cotton was 100 mg/l (Li et al.…”
Section: Resultsmentioning
confidence: 99%
“…These values are near or below those estimated for imidacloprid in other insects. Thus, the LD 50 of imidacloprid in the migratory grasshopper, Melanoplus sanguinipes (F.), was 53 mg/l for the oral applications (Tharp et al. 2000), while its LC 50 in the adult whiteflies collected from Arizona cotton was 100 mg/l (Li et al.…”
Section: Resultsmentioning
confidence: 99%
“…While our reported LD50 is high it may be due to the delivery method, toxicological endpoint, and metabolism. Grasshoppers ( Melanoplus sanguinipes ) sustain a long period of “debilitation” before death, with high oral and contact LD50s of 53.38 and 96 ppm (µg/g), respectively, for IMD at 72 hours after treatment 47 . In honeybees, mortality is delayed from high doses of IMD, compared to moderate doses 48 , prompting use of a 96 h endpoint.…”
Section: Discussionmentioning
confidence: 99%
“…Approximately 1 hour after treatment, the DCMD again responded to the looming stimulus in a stable manner (post-effect phase) that was maintained until the end of the recording period, two hours and 20 minutes after treatment. Acute behavioural effects of IMD toxicity include periods of trembling and sporadic movements of the abdomen and legs, followed by paralysis in the honeybee ( Apis mellifera ) 17 , flea ( Ctenocephalides felis ) 56 , beetle ( Tenebrio molitor ) 57 , and grasshopper ( Melanoplus sanguinipes ) 47 . Our results are consistent with other studies that found initial neuronal effects to be hyperexcitation followed by neural silence 57, 58 , which may be attributed to receptor desensitization 12, 59 .…”
Section: Discussionmentioning
confidence: 99%
“…Leaf discs treated with imidacloprid and then fed to the migratory grasshopper Melanoplus sanguinipes (Fabr.) produced a lower LD 50 than topical applications (Tharp et al 2000). For Piper extracts, toxicity will occur mainly through consumption of, rather than contact with, treated plant material, which will help conserve beneficial nontarget insects exposed to the extracts.…”
Section: Discussionmentioning
confidence: 99%